(untitled) (Linguostylistic Studies, 2021)
The study argues that the dirges recorded in the Podilia region in the 21st century and according to the credible sources, documented by Metropolitan Hilarion and Hilarion Sventsitskyi, are the works of medieval monks who were also poets. They present both Christian and pagan conceptions of the world. The funeral songs are the best illustration of it, represented in symbols and rites. Among pagan symbols, the most common are: 1) trees that were once planted on graves (guelder rose, birch) and that later became a prototype for cross and resurrection; 2) birds that were supposed to come to these trees (e.g. cuckoo, cranes migrating south, a place where the souls of the dead went to according to pre-Christian beliefs and other birds (non-specified); 3) comprehensive description of the grave as a house of rest on a day of the funeral and on the dates of remembrance, a week after God’s Resurrection on Thomas Sunday, or as in a pagan rite of remembrance, during Midfeast of Pentecost; 4) conceptual symbol of road/way, which is actively mentioned in lyrics when a dead body is carried/taken to the graveyard. It is yet another evidence for a pre-Christian tradition that lives on keeping to the detailed instructions to the rite procedure; 5) another pagan conceptual symbol is bread. It has always accompanied the dead on their last way. The topic of the ritual meal is present in the funeral songs as it is an integral part of the funeral ceremony. The ritual meal echoes with the pre-Christian belief that Soul has to be satisfied so that it would not take an act of revenge on relatives. That is why a remembrance meal is held on the day of the funeral, on the 9th and 40th days after burying, and on the anniversary. In addition, the evidence of the merging of paganism and Christianity is Apocrypha sung at the funeral. The plot of these songs describes the Way of the Cross and empathy of Christ’s disciples and depicts comprehensively (including fragments with dialogues) the behavior model of the Mother of God. The study considers the motives of the dirges texts, topical in ancient eastern and western rites, and argues that they mostly contain an appeal to God, to the Mother of God, longing for the dead, warnings for the living.